2005
DOI: 10.1007/s10750-005-4449-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Patterns of Protozoan Communities in a Meso-eutrophic Reservoir (Esch-sur-Sûre, Luxembourg)

Abstract: The spatio-temporal distribution of the heterotrophic nanoflagellates (HNF) and ciliates was monitored in the reservoir of Esch-sur-Suˆre during the year 1999. Three main periods of protozoan development were observed, in early April, early May, and in July. On the basis of the seasonal dynamics, it appeared that the early spring development of protozoa was probably not controlled by resources or predators. The second protozoan development was progressively controlled by the increase of metazooplankton density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
(49 reference statements)
2
7
0
Order By: Relevance
“…Oligotrichs are often reported as relatively common components of lacustrine protozooplankton, especially in the epilimnion (Zingel & Ott 2000, Zingel 2005). The vertical distribution reported here is similar to that observed by Műller et al (1991) in Lake Constance in Germany, and that seen in Esch-sur-Sure reservoir in Luxemburg (Jacquet et al 2005). The abundance of haptorids, most of which are known as predators, was highest in the epilimnion.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Oligotrichs are often reported as relatively common components of lacustrine protozooplankton, especially in the epilimnion (Zingel & Ott 2000, Zingel 2005). The vertical distribution reported here is similar to that observed by Műller et al (1991) in Lake Constance in Germany, and that seen in Esch-sur-Sure reservoir in Luxemburg (Jacquet et al 2005). The abundance of haptorids, most of which are known as predators, was highest in the epilimnion.…”
Section: Discussionsupporting
confidence: 87%
“…The bacterivorous Scuticociliatida were most abundant in the intermediate and deep layers, in harmony with bacterial densities in the hypolimnion, and probably also resulting from their tolerance to low oxygen concentrations. It is suggested that scuticociliates are more effective grazers at lower temperatures (Schőnberger 1994, Simek et al 1998, Jacquet et al 2005, which may be a further reason for their dominance in the deeper layers. In the meta-and hypolimnion, the abundance of metazooplankton that potentially prey on small-sized ciliates, tends to decrease with depth (Műller et al 1991, Zingel 2005, which may explain the high abundance of scuticociliates in the deeper layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterivorous and omnivorous ciliates were more abundant in the bottom wa− ters. This vertical micro−distribution of algivorous and bacterivorous ciliates was similar to that previously observed in shallow lakes (Jacquet et al 2005). In this study, ciliates community was mainly composed of genera Prorodon, Oxytricha and Cinetochilum.…”
Section: Discussionsupporting
confidence: 90%
“…The ability of the protists to rapidly respond to an increase in bacterial abundance could have contributed to the unusually low recovery of bacterial DNA from time points immediately following the removal of carvone (days 7, 12, 22). Jacquet et al (2005a, b) report that numbers of protozoa, comparable to that in the carvone treatments, removed up to 7.8% of bacteria in 24 h whereas Domaizon et al (2003) describe per capita grazing rates from 1.2 × 10 3 to 5.1 × 10 6 bacteria L −1 h −1 for heterotrophic flagellates and from 4.8 × 10 6 to 6.8 × 10 7 bacteria L −1 h −1 for mixotrophic flagellates. Hence, grazing by protists might have masked the otherwise rapid increase in microbial growth upon the addition of carvone.…”
Section: Resultsmentioning
confidence: 98%